A Wearable Aptamer Microneedle Patch for Minimally-Invasive Therapeutic Drug Monitoring - Lin, Shuyu; Zhu, Jialun; Cheng, Xuanbing; Milla, Carlos; Emaminejad, Sam (Meeting abstracts (Electrochemical Society), 2022)
To realize personalized medicine, the right drug needs to be delivered to the right patient at the right dose. However, it is extremely challenging to dose drugs with narrow therapeutic windows (e.g., antibiotics). For these drugs, due to the small difference between ineffective and toxic concentration levels, the prescribed dosage may result in a circulating concentration outside the therapeutic window, leading to toxicity ( e.g. , kidney injury) and/or ineffective pharmacotherapy. To prevent such adverse events, patients under these medications are committed to therapeutic drug monitoring (TDM), which in the current clinical practice involves repeated and invasive blood draws followed by labor-intensive and high-cost lab-based analyses ( e.g. , chromatography, immunoassay). The turnaround times for results are prolonged, and thus, inadequate to allow for timely intervention. Wearable pharmaceutical sensing systems—capable of tracking the medication’s concentration in a continuous and non-/minimally-invasive manner—are well-suited to address these challenges encountered in current TDM practice. To establish a generalizable wearable TDM modality for a broad range of pressing clinical applications, we focus on tracking pharmaceuticals in interstitial fluid (ISF). The choice for ISF is motivated by noting that a wide panel of pharmaceuticals, particularly those with stringent personalized dosing requirements, partition into ISF with high correlation to their circulating levels. To target these analytes, microneedles emerged as promising tools, which are capable of overcoming the skin barrier to directly access ISF in a minimally-invasive manner without user intervention. By integrating sensors on microneedle substrates ( e.g. , on-the-tip electrochemical sensor fabrication), ISF analytes can be monitored continuously. However, currently demonstrated in-situ ISF sensors are mainly based on enzymatic sensing, which significantly limits the scope of target analytes to the ones with enzymes available. Overcoming this limitation, we devised a low-cost affinity-based biosensor-on-needle fabrication scheme, which was utilized to develop an aptamer microneedle patch (AMPatch). Our AMPatch consists of: 1) a microneedle electrode substrate based on repurposed acupuncture gold needles, leveraging the validated skin puncture performance and the high conductivity of these needles; 2) a gold nanoparticle (AuNP) coating, rendering a high-quality gold surface (comparable to standard electrodes used in electrochemistry) for strong and compact aptamer immobilization; and 3) an aptamer/signal reporter self-assembled monolayer, transducing the target binding events into measurable electrical readouts. We specifically target tobramycin, an antibiotic with a narrow therapeutic window and large intra-subject pharmacokinetic variations, which in the current clinical practice requires multiple TDM sessions to achieve an optimal dosing. Leveraging the developed AMPatch, we demonstrated real-time continuous monitoring of tobramycin ex-vivo (in a phantom gel model, mimicking the dermal ISF testing scenario) and in-vivo (via rat studies). Our results demonstrate the suitability of the AMPatch for minimally-invasive monitoring of the target drug’s pharmacokinetic profile and its potential as a viable TDM tool for personalized pharmacotherapy. Acknowledgements: This work was supported by the National Science Foundation (Award 1847729) and the UCLA Innovation Fund.